Misconceptions on Fractions, Algebraic Variables, and Functions in Mathematics Education: A 2016-2026 Systematic Literature Review of Prevalence, Root Causes, and Intervention Effectiveness - Riska Indah Lestari; Tatang Herman; Suhendra Suhendra; Tia Purniati (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2026)
Misconceptions in mathematics education are a persistent problem with far-reaching implications across all levels of education, from preschool through higher education. This study narrows the focus on misconceptions to three main clusters that are frequently encountered and have the greatest impact on mathematics education: fractions, algebraic variables, and functions. This study aims to identify the most common forms of misconceptions, their underlying patterns, and interventions proven effective in reducing misconceptions within these three priority clusters. Using a Systematic Literature Review (SLR) approach in accordance with the PRISMA 2020 guidelines, the search was conducted across three databases, such as Scopus, ERIC, and SpringerLink, yielding 117,846 initial records. Following a multi-stage screening process, 31 articles published between 2016 and 2026 were analysed in depth. The review results indicate that the most prevalent misconceptions are related to fractions, algebraic variables, and functions. Regarding interventions, the use of technological tools such as GeoGebra, inquiry-based learning, cognitive conflict, and a bilingual approach was frequently found to have demonstrated positive effects across studies. These findings have important implications for curriculum design, teacher professional development, and the design of learning environments that are adaptive and responsive to the diversity of students’ prior conceptions.